Variability of Agronomic Valuable Traits of Cotton Lines Depending on the Genotype and Vegetation Conditions in Different Ecological Zones (Texas Journal of Agriculture and Biological Sciences, 2023)
In addition, the characteristics of lines in different soil-climatic zones are given in accordance to the magnitude of variability and homeostaticity of the studied traits. The data of two-factor analysis of variance on the relative share of genotypic, environmental, and variability caused by the interaction of growing conditions × genotype in the general phenotypic variation of the trait are presented. According to the results of two-factor analysis of variance of cotton lines, it was revealed that the point of cultivation was the main factor that influenced the variability of the studied traits, the contribution of which, depending on the agronomic valuable trait, was 36.5-99.4%.